Asymmetric Dehydrative C-, N-, and O-Allylation Using Naph-diPIM-dioxo-i-Pr–CpRu/p-TsOH Combined Catalyst - Miyata, Kengo; Kitamura, Masato (Synthesis, 2012)
(S,S)- or (R,R)-Naph-diPIM-dioxo-i-Pr–CpRu(II) complex with a Brønsted acid catalyzes dehydrative intermolecular C-allylation with high enantio- and regioselectivity. The new soft Ru/hard H+ combined catalyst can also be used for intramolecular C-, N-, and O-allylations, giving nearly enantiomerically pure α-alkenyl-substituted cyclic compounds. As water is only the co-product, the synthetic process can be readily scaled up.
Keywords: dehydrative allylation; asymmetric catalysis; cyclopentadienyl ruthenium; chiral bidentate sp2N ligand